(untitled) (Research, Society and Development, 2022)
pathological course, several complications and the main one is the acute respiratory syndrome. However, it also involves other systems and, among them, the ophthalmological. When correlating viral syndromes with ocular infections, the prominence of viral conjunctivitis and, therefore, the probabilities of conjunctivitis associated with SARS-CoV-2 is shown. Then, the aim of this study was to verify the population’s concern regarding the involvement of COVID-19 with ophthalmological complications, with a survey carried out through epidemiological analysis based on the Google Trends platform. The study suggests, therefore, the importance of tools in the context of Big Data, for the dissemination of information, especially in the current period of the pandemic, by enabling research concerning the current status of health indicators, even without carrying out data collection in the field. So, the conclusion is, based on the data collected in the tool used, that the population’s interest in topics related to COVID-19 and ophthalmological symptoms is expressive, which can signal to the competent areas the need to develop strategies for the dissemination of guidelines, as well as the deepening of discussions on these themes.